2017
DOI: 10.1044/2017_jslhr-h-17-0030
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Objective and Subjective Speech Perception in Complex Listening Environments

Abstract: Purpose: A frequent complaint by older adults is difficulty communicating in challenging acoustic environments. The purpose of this work was to review and summarize information about how speech perception in complex listening situations changes across the adult age range. Method: This article provides a review of age-related changes in speech understanding in complex listening environments and summarizes results from several studies conducted in our laboratory. Results: Both degree of high frequency hearing lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 85 publications
(117 reference statements)
1
34
0
Order By: Relevance
“…Overall, speech understanding was significantly worse for middle-aged adults compared to young adults, measured both behaviourally and via self-report, even after controlling for group differences in PTA and high frequency hearing thresholds. This confirmed pervious research on the adverse effect of age on speech perception (Helfer et al 2017).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, speech understanding was significantly worse for middle-aged adults compared to young adults, measured both behaviourally and via self-report, even after controlling for group differences in PTA and high frequency hearing thresholds. This confirmed pervious research on the adverse effect of age on speech perception (Helfer et al 2017).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we investigated how age affects speech understanding and cognitive effort during multitasking in the 'Audio-Visual True-to-life Assessment of Auditory Rehabilitation'paradigm (AVATAR) (Devesse et al 2019). Typically, the effect of age on effort is studied in adults over 60 years of age, but studies including middle-aged adults showed that hearing difficulties and listening effort already start to increase from the fourth decade of life onwards (Degeest et al 2015;Helfer et al 2017). Therefore, we compared outcome scores of middleaged normal hearing adults with scores of young adults tested previously with AVATAR.…”
Section: Introductionmentioning
confidence: 99%
“…However, a large minority of people aged over 45 years have some difficulty hearing (Cruickshanks et al, 1998;Feder et al, 2015;Helfer et al, 2017): Clinical hearing loss is typically diagnosed decades after people first experience real-life issues such as trouble understanding speech in the presence of background sound (Pichora-Fuller and Levitt, 2012;Pichora-Fuller et al, 2016). These issues with hearing make communication more difficult (Pichora-Fuller, 2003;Pichora-Fuller et al, 2016), increasing the risk for social isolation (Weinstein and Ventry, 1982;Mick et al, 2014;Shukla et al, in press), which, in turn, contributes to other poor health outcomes (Nicholson, 2009), including an increased risk of cognitive decline (Fratiglioni et al, 2000;Lin and Albert, 2014;Chern and Golub, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In general, traditional measures are a simplification of daily listening situations (Tun et al 2012;Helfer et al 2017) and might therefore underestimate the amount of cognitive resources allocated during listening, also referred to as listening effort. According to a recent consensus paper, listening effort refers to 'the deliberate allocation of mental resources to overcome obstacles in goal pursuit when carrying out a listening task' (Pichora-Fuller et al 2016).…”
Section: Introductionmentioning
confidence: 99%